Human Skeletal Muscle Fiber Type Specific Protein Content - Galpin, Andrew J. (2012)
The aim of this project was to develop a method to assess fiber type specific protein content across the continuum of human skeletal muscle fibers. Individual vastus lateralis muscle fibers (n = 264) were clipped into two portions, one for SDS-PAGE fiber typing and one for Western blot protein identification. Following fiber type determination, fiber segments were combined into fiber type specific pools (~20 fibers/pool) and measured for total protein quantity, GAPDH, citrate synthase, and total p38 content. GAPDH content was 64%, 54%, 160%, and 138% more abundant in MHC I/IIa, MHC IIa, MHC IIa/IIx, and MHC IIx fibers when compared to MHC I. Inversely, citrate synthase content was 528%, 472%, 242%, and 47% more abundant in MHC I, MHC I/IIa, MHC IIa, and MHC IIa/IIx fibers when compared to MHC IIx. Total p38 content was 87% greater in MHC IIa versus MHC I fibers. These data and approach establish a reliable method for human skeletal muscle fiber type specific protein analysis. Initial results show particular proteins exist in a hierarchal fashion throughout the continuum of human skeletal muscle fiber types, further highlighting the necessity of fiber type specific analysis.